Spectroscopic study on the complexation of trivalent actinide and lanthanide ions with TEDGA in solution - Sittel, Thomas; Meißner, Maximilian; Keller, Max; Geist, Andreas; Panak, Petra (European journal of inorganic chemistry, 2024)
NMR spectroscopy studies on the complexation of La(III), Sm(III), Lu(III), Y(III) and Am(III) with N,N,N′,N′-tetraethyldiglycolamide (TEDGA) have been performed. Initial studies concerning the stoichiometry of the complexes prove the formation of [M(TEDGA)3]3+ in D2O and [M(TEDGA)1-3]3+ in CD3CN. Decreasing the solvent polarity translates to an increase of the complex stability as shown by complementary TRLFS studies with Cm(III). Due to delocalization of the lone electron pair of the amide nitrogen atom, the M(III)−O interaction has been studied indirectly by collecting 13C and 15N NMR data. The observed chemical shifts prove that the interaction of the trivalent ions, An(III) and Ln(III), and TEDGA is almost identical.
Zuerst veröffentlicht: 18. Januar 2024
Gesehen am 10.06.2024